Numerical Calculations and Time Evolution of Coherent States Wave Functions of Charged Oscillator in Magnetic Field - Mohsen, W.R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The wave functions of the coherent states of the charged oscillator in magnetic field are obtained via a canonical transformation. The numerical calculations of these functions are made and then the space and time plots are obtained. It was shown that these states are Gaussians distributions of widths vary periodically in an opposite way with their peaks. We interpret that is due to the mutual actions of the spreading effect of the wave packet and the reaction of the magnetic field.